Status on lattice calculations of the proton spin decomposition - Keh-Fei Liu (AAPPS Bulletin, 2022)
Abstract Lattice calculations of the proton spin components is reviewed. The lattice results of the quark spin from the axial-vector current matrix element at ∼ 0.3−0.4 is smaller than those from the constituent quark models. This is largely due to the fact that the vacuum polarization contribution from the disconnected insertion is negative. Its connection with the anomalous Ward identity is clarified and verified numerically. This resolves the contentious issue in the “proton spin crisis.” The glue spin and angular momentum are found to be large and there is notable contribution from the quark orbital angular momentum. Renormalization, mixing, and normalization of the quark and glue angular momenta are discussed. With sufficient precision, they can be compared with more precise experimental measurements when the electron-ion collider facility is available.